National Jail Census, 1983 ([Verlag nicht ermittelbar], 1985)
The National Jail Census was conducted by the United States Bureau of the Census for the Bureau of Justice Statistics. The census was taken of all locally administered county and municipal jails with the authority to hold prisoners for more than 48 hours. Data are presented for 3,338 jails in 45 states. Excluded are Connecticut, Delaware, Hawaii, Rhode Island, and Vermont. Information includes jail population by legal status, age and sex of prisoners, maximum sentence, admissions and releases, available services, structure and capacity, expenditure, and employment.